Proposal and validation of a new classification for trochanteric fractures based on medial buttress and lateral cortical integrity - Zhang, Yiran; Zhang, Fengshi; Li, Ci; Zhang, Meng; Zhang, Peixun (Frontiers in Surgery, 2023)
Background: Trochanteric fractures usually require surgical treatment. The currently used classification system, such as AO classification, cannot cover all variant types, and is poor in reliability, causing confusion in surgical decision making. This study describes a simple, well-covered, re-liable, accurate, and clinically useful classification. Methods: We retrospectively reviewed the records of 907 patients with trochanteric fractures treated by us from 1999 to 2019 and proposed a new classification according to radiographs. Then, 50 records randomly selected in proportion were examined by 10 observers (5 experienced and 5 inexperienced) independently according to AO and the new classification. After a two-week interval, repeat evaluation was completed. The Kappa coefficient was used to investigate the intra-observer reliability, inter-observer reliability and the agreement between the observers and the “reference standard”. Results: The new classification system includes 12 types composed of 3 medial groups and 4 lateral groups. According to the medial buttress, the fractures are divided into group I (intact lesser trochanter, adequate but-tress), group II (incomplete lesser trochanter, effective cortical buttress after reduction) and group III (huge defect of the medial cortex). According to the penetration region of the lateral fracture line, the fractures are divided into group A (intact lateral cortex), group B (incomplete lateral cortex), group C (subtrochanteric fractures) and group D (multiple lateral fracture lines). All of the included cases can be classified according to the new classification, of which 34(3.75%) cases are unclassifiable by the AO classification. Intra-observer: The experienced achieved substantial agreement using both AO (k=0.61[95% confidence interval 0.46-0.76]) and new classification (k=0.65[0.55-0.76]). The inexperienced reached moderate agreement using both AO (k=0.48[0.33-0.62]) and new classification (k=0.60[0.50-0.71]). Inter-observer: The overall reliabilities for AO(k=0.51[0.49-0.53]) and for new classification (k=0.57[0.55-0.58]) were both moderate. The agreement between the experienced and the reference standard according to AO (k=0.61[0.49-0.74]) and new classification (k=0.63[0.54-0.72]) were both substantial. The agreement between the inexperienced and the reference standard according to AO (k=0.48[0.45-0.50]) and the new classification (k=0.48[0.41-0.54]) were both moderate. Conclusion: Compared with AO classification, our new classification is better in coverage, reliability and accuracy, and has the feasibility of clinical verification and promotion.